Genome-partitioning strategy, plastid and nuclear phylogenomic discordance, and its evolutionary implications of Clematis (Ranunculaceae) - Xiao, Jiamin; Lyu, Rudan; He, Jian; Li, Mingyang; Ji, Jiaxin; Cheng, Jin; Xie, Lei (Frontiers in Plant Science, 2022)
Clematis is one of the large genera of Ranunculaceae with many phylogenetic problems remaining to be resolved. Previous studies based on Sanger sequencing data, plastid genome data, and nrDNA sequences did not well resolve the phylogeny of Clematis. Species of Clematis have considerable genome size of more than 7 Gbp, which brings difficulties of using genome skimming data for phylogenetic analysis. In this study, we used genome skimming data of low sequencing depth and transcriptome data to assemble plastid genome sequences, nuclear single nucleotide polymorphism (SNP) datasets, and single-copy nuclear orthologous genes (SCOGs) to reconstruct the phylogenetic backbone of Clematis, and test effectiveness of these genome partitioning methods. We also further analyzed the discordance among nuclear gene trees and between plastid and nuclear phylogenies. The results showed SCOG dataset derived from transcriptomes well resolved the phylogenetic backbone of Clematis, and the nuclear SNP sequences from low-depth genome skimming data can also produce a similar result with SCOG data. In contrast to the plastid phylogeny, the phylogeny resolved by nuclear genome data is more robust and well corresponding to morphological characters. Our results suggested that rapid species radiation generated high level of incomplete lineage sorting, which was the major cause of nuclear gene discordance. Moreover, the simulation showed that there were also interspecific hybrid events causing a lot of cyto-nuclear discordance in Clematis. This study not only provided a robust phylogenetic backbone of Clematis based on nuclear genome data, but also presented suggestions of genome partitioning strategies for the phylogenomic study of plant taxa.